Optimisation of surface measurement for metal additive manufacturing using coherence scanning interferometry - Gomez, Carlos; Su, Rong; Thompson, Adam; DiSciacca, Jack; Lawes, Simon; Leach, Richard K. (SPIE, 2017)
Surface topography measurement for metal additive manufacturing (AM) is a challenging task for contact and non-contact methods. In this paper, we present an experimental investigation of the use of coherence scanning interferometry (CSI) for measurement of AM surfaces. Our approach takes advantage of recent technical enhancements in CSI, including high dynamic range for light level and adjustable data acquisition rates for noise reduction. The investigation covers several typical metal AM surfaces made from different materials and AM processes. Recommendations for measurement optimisation balance three aspects: data coverage, measurement area and measurement time. This study also presents insight into areas of interest for future rigorous examination, such as measurement noise and further development of guidelines for the measurement of metal AM surfaces.